EDUKASI BUKU KAS HARIAN MENUJU KEUANGAN STABIL DAN MASA DEPAN CERAH BAGI REMAJA PANTI ASUHAN ADINDA - Evelyn Anggita Ronauli Lumban Gaol; Mochamad Yusuf Fitra Syam; Arul Aditia; Nia Novita Sari (Jurnal Abdi Citra, 2026)
The community service activity entitled “Daily Cash Book Education toward Financial Stability and a Brighter Future for Adolescents at Adinda Orphanage” was conducted at Adinda Orphanage, Cengkareng Barat. This activity aimed to enhance basic financial literacy through the introduction of simple financial record-keeping using a daily cash book. The participants were children aged 5–12 years living at the orphanage. The implementation methods included interactive lectures, question-and-answer sessions, and the provision of daily cash book examples as learning media. The materials were delivered systematically and adjusted to the participants’ level of understanding. The results showed an improvement in participants’ understanding of basic financial concepts, particularly income and expenses, as well as increased awareness of the importance of financial recording in daily life. Overall, this activity was effective as an initial step in fostering structured and responsible financial management habits from an early age.